Effects of Different Media and Organic Additives Interaction on In Vitro Regeneration of Dendrobium Orchid - Aktar, S; Nasiruddin, KM; Hossain, K (Journal of Agriculture & Rural Development, 2008)
Interaction of different media and organic additives showed significant effects on growth and development of protocorm like bodies (PLBs) and subsequent plantlets regeneration of Dendrobium orchid in laboratory conditions. Except the length of shoots and leaves, the highest values of all parameters were obtained from the interaction of ½MS medium with Sabri banana pulp. However, the longest shoots were found in KC medium with Sabri banana pulp and the longest leaves were found in both KC and ½MS media with Sabri banana pulp. Key words: Interaction, regeneration, Dendrobium, media and organic additives. doi:10.3329/jard.v6i1.1659 J Agric Rural Dev 6(1&2), 69-74, June 2008